An fMRI study of the social competition in healthy subjects - Polosan, M.; Baciu, M.; Cousin, E.; Perrone, M.; Pichat, C.; Bougerol, T. (Brain and cognition, 2011)
► Focus on social competition requiring both executive functions (inhibition) and theory of mind. ► Use of an original paradigm contrasting inter-human to human–machine interactions. ► Highlight the regions of the inhibition cerebral network modulated by the theory of mind. ► Interest in studying psychiatric disorders characterized by executive and social dysfunction. Social interaction requires the ability to infer another person’s mental state (Theory of Mind, ToM) and also executive functions. This fMRI study aimed to identify the cerebral correlates activated by ToM during a specific social interaction, the human–human competition. In this framework, we tested a conflict resolution task (Stroop) adapted to a virtual situation of competition. The participants were instructed to play in order to win either against a human-like competitor (human–human competition) or against a non-human competitor (human–machine competition). Only the human–human competition requires ToM as this type of competition is performed under social interaction. We identified first the classical network of executive regions activated by Stroop. Secondly, we identified the social (human–human) competition regions, represented by the bilateral superior and inferior frontal gyri, the anterior cingulate, the insula, the superior and anterior temporal, the hippocampus, the fusiform gyrus, the cuneus and the precuneus. Finally, we identified the executive regions that were modulated by the human–human competition, i.e., the executive control regions additionally activated when mentalizing in the context of social competition. They constituted a network predominant to the right and composed of the superior and middle frontal, anterior cingulate, insula and fusiform gyrus. We suggest that our experimental paradigm may be useful in exploration of the cerebral correlates of social adjustments in several situations such as psychiatric disorders presenting executive and social dysfunctions.